Regional Tax Compliance Analysis of PB1 in Pangkalpinang - Pipin, Pipin; Aprilian, Rahil Imainul; Suciati, Fardillah; Elista, Irma (Equity: Jurnal Ekonomi, 2025)
This study aims to evaluate the extent to which the installation of tax banners as media of socialization can improve tax compliance among cafe and restaurant business actors in Pangkalpinang City. Restaurant tax (PB1) is an important contributor to local revenue, with revenue achievements in 2023 amounting to IDR 27.3 billion or 21.7% of total local revenue. This study uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation studies. The research sample includes 1-10 cafe and restaurant owners who have installed tax banners and routinely pay PB1. The research findings indicate that tax banners act as a visual reminder and educational media for consumers, although their influence on business actors is relatively limited. Banners are considered effective in increasing the timeliness of tax reporting, but do not have a significant impact on the amount of tax payments. The SWOT analysis reveals that banners have the advantage of being a cost-effective means of information and physical evidence of compliance, but also have weaknesses such as limited information space and the risk of "banner blindness". This study concludes that the installation of banners has a positive impact on tax compliance, although optimization efforts are still needed through more intensive socialization and periodic policy evaluation. The recommendations put forward include the need for further research with a quantitative approach and expanding the scope of research objects to obtain more comprehensive findings.